2007
DOI: 10.1007/s00213-007-1012-8
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal endocannabinoids inhibit spatial learning and limit spatial memory in rats

Abstract: Systemic Rimonabant-induced deficits are due to anxiogenic properties of the drug. The difference between administration regimes is discussed in terms of CB(1) receptor blockade in multiple non-memory and memory-related brain regions and the possibility that selective inactivation of hippocampal CB(1) receptors may be memory enhancing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 47 publications
(61 reference statements)
3
33
0
2
Order By: Relevance
“…Contribution of the endocannabinoid system in the hippocampus is supported by a recent study (438). From a clinical aspect, these studies give a warning to the use of cannabinoid agonists and antagonists to human patients, since it may have adverse side effects on hippocampal functions.…”
Section: Spatial Memorymentioning
confidence: 83%
“…Contribution of the endocannabinoid system in the hippocampus is supported by a recent study (438). From a clinical aspect, these studies give a warning to the use of cannabinoid agonists and antagonists to human patients, since it may have adverse side effects on hippocampal functions.…”
Section: Spatial Memorymentioning
confidence: 83%
“…Some studies reported that intrahippocampal infusions of cannabinoid agonists impair either the encoding or consolidation of memory of water-maze spatial, inhibitory avoidance, or object recognition training (33,34), whereas others found enhancing effects (35). Moreover, it has been reported that the CB1 receptor antagonist AM251 infused into the hippocampus impairs memory consolidation of inhibitory avoidance training (36).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, genetic and pharmacological blockade of CB1 leads to deficits in extinction processes (877), whereas the selective inactivation of hippocampal CB1 may enhance memory (730). Pharmacologically elevated AEA levels through FAAH inhibition impair hippocampal-dependent learning and memory tasks (45), and blockade of 2-AG hydrolysis interferes with memory performance (307).…”
Section: Spatial Memorymentioning
confidence: 99%